2019
DOI: 10.1109/jeds.2019.2931614
|View full text |Cite
|
Sign up to set email alerts
|

Flexible IGZO TFTs and Their Suitability for Space Applications

Abstract: In this paper, low earth orbit radiation (LEO), temperature, and magnetic field conditions are mimicked to investigate the suitability of flexible InGaZnO transistors for lightweight space wearables. More specifically, the impacts of high energetic electron irradiation with fluences up to 10 12 e − /cm 2 , low operating temperatures down to 78 K and magnetic fields up to 11 mT are investigated. This simulates 278 h in LEO. The threshold voltage and mobility of transistors that were exposed to e − irradiation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Apart from temperature sensing and physiological monitoring applications, a-IGZO TFT based circuits have been used in other applications such as radiation sensing [82], magnetosensory applications [92], space applications [93], gamma ray detection [94], NO 2 gas sensing [95] etc. Moreover, IGZO TFTs have also been utilized as sensing devices in an aqueous medium for applications such as biosensing [96], virus detection [97], and artificial DNA detection [98] etc.…”
Section: Sensor Acquisition Systems Based On A-igzo Tftsmentioning
confidence: 99%
“…Apart from temperature sensing and physiological monitoring applications, a-IGZO TFT based circuits have been used in other applications such as radiation sensing [82], magnetosensory applications [92], space applications [93], gamma ray detection [94], NO 2 gas sensing [95] etc. Moreover, IGZO TFTs have also been utilized as sensing devices in an aqueous medium for applications such as biosensing [96], virus detection [97], and artificial DNA detection [98] etc.…”
Section: Sensor Acquisition Systems Based On A-igzo Tftsmentioning
confidence: 99%
“…Utilization of electronic devices not only involve everyday usage, such as smartphones or computers, but also application in certain environments and purposes. As human society has started to expand its field of interest in space exploration and alternative energy production, the use of electronic devices in harsh radiation environments has increased over the past decades and is expected to grow even more dramatically. For example, increased space activity and the development of civilian space programs, such as SpaceX, have boosted the popularity of the space industry and given rise to the development of radiation-resistant large-area devices for future space equipment. , Radiation-resistant electronic devices are also needed in nuclear power plants where radioactive waste is discharged . Ionizing radiation is not only problematic for electronic devices that are intended for such missions or safety-critical applications but also for general semiconductor devices, in which daily radiation exposure has become a serious problem. , Presently, as the dimensions of electronic circuits are becoming ever smaller, with certain components becoming nano-scaled, faulty products may result from cosmic radiation during the air transportation with high altitudes .…”
Section: Introductionmentioning
confidence: 99%
“…1−4 For example, increased space activity and the development of civilian space programs, such as SpaceX, 5 have boosted the popularity of the space industry and given rise to the development of radiation-resistant large-area devices for future space equipment. 6,7 Radiation-resistant electronic devices are also needed in nuclear power plants where radioactive waste is discharged. 8 Ionizing radiation is not only problematic for electronic devices that are intended for such missions or safety-critical applications but also for general semiconductor devices, in which daily radiation exposure has become a serious problem.…”
Section: Introductionmentioning
confidence: 99%
“…The performances of a-IGZO TFTs fabrication on flexible substrate during tensile and compressive strain are extensively reported Park et al (2009), Munzenrieder et al (2011), Hasan et al (2017), Billah et al (2017), Münzenrieder et al (2013). In addition to the mechanical stability, the electrical stability at any environmental condition (light exposure, moisture, temperature (T), relative humidity (RH)) is a key aspect for the employment of a-IGZO TFTs on a large scale Costa et al (2019). Although different studies concerning the effects of the RH on the IGZO TFT operation have proved a reliable variation for the threshold voltage Knobelspies et al (2018), Lee and Jeong (2018), Kim et al (2017), no common trend in the variations of the other parameters was observed.…”
Section: Introductionmentioning
confidence: 99%